A living death: Zimbabwean migrants in the UK who are forced apart from their children - Madziva, Roda (2011)
This thesis is concerned with the lived experience of nineteen Zimbabwean migrants I interviewed in the UK who were forced apart from their children for a lengthy period of time by the UK immigration system. It explores the processes through which these migrants were rendered rightless in their country of birth where their government directly threatened their physical lives and how they were forced to migrate to the UK without their children in search of human rights and protection. However, upon arrival in the UK, these migrants' rightlessness was reinforced as the UK immigration and asylum law affords only the most minimal of rights to asylum seekers and other categories of forced migrants.